Infected Pseudoaneurysm of the Superficial Femoral Artery in a Patient with Salmonella enteritidis Bacteremia - MA Hussain; G Roche-Nagle (Canadian Journal of Infectious Diseases and Medical Microbiology)
Mycotic aneurysms, defined as irreversible dilation of an artery due to destruction of the vessel wall by infection, are rare but are associated with a high risk of rupture if not treated promptly. The case of a healthy 52-year-old smoker who presented with pyrexia, rigors, night sweats and severe right leg pain with swelling is presented. He was diagnosed with a superficial femoral artery mycotic aneurysm, with Salmonella enteritidis as the causative agent. He was treated with high-dose antibiotics, local debridement and autologous reconstruction. A high index of suspicion is needed to make the correct diagnosis in these cases. Prompt surgical intervention and antimicrobial therapy are the cornerstones of treatment to reduce the associated high morbidity and mortality.